HUBUNGAN JUMLAH ANGKA LEMPENG TOTAL DENGAN JUMLAH ANGKA ENDOTOKSIN PADA AIR REVERSE OSMOSIS HEMODIALISA - Rita Yuliati; Misbahul Subhi; Ike Dian Wahyuni (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2025)
Reverse Osmosis water is a major component in the hemodialysis process, acting as a solvent for dialysate fluid. The microbiological quality of Reverse Osmosis water significantly impacts patient safety, particularly with regard to endotoxin contamination originating from the cell walls of Gram-negative bacteria. This 2025 study aimed to analyze the relationship between total plate count (ALT) and endotoxin levels in Reverse Osmosis water in the hemodialysis unit of Hospital X, Mojokerto City. This study used an analytical observational design with a cross-sectional approach. Samples were obtained from a single location, namely water produced by the Reverse Osmosis machine that was ready to be flowed into the hemodialysis machine. Sampling was carried out 20 times, 10 samples of Total Plate Count and 10 samples of Endotoxin for five consecutive days at two different times each day, namely the morning shift (around 08.00–10.00) and the afternoon shift (around 13.00–15.00). ALT was examined using the pour plate method, and endotoxin levels were measured with the Nexgen device using the chromogenic LAL method. Based on the Spearman test results, a correlation coefficient (r) value of -0.518 was obtained with a significance value (p) of 0.125 (p > 0.05), which indicates that there is a moderate negative relationship between ALT and endotoxin levels, but this relationship is not statistically significant at the 95% confidence level (α = 0.05). Therefore, in this study, changes in the Total Plate Count (ALT) did not affect the amount of endotoxin.